The incorporation of Ricardo Palma to the Hispanic Society of America in 1907 and correspondence taken until 1917 - Mera, Arnaldo (2019)
Looking through unpublished correspondence between the Hispanic Society of America (HSA) and the author Ricardo Palma, we could find eight signed letters by him, a note without signing and a membership form also signed and required after four years since his involvement in this institution in 1907. All this already mentioned gives an insight into an unknown period of his academic and professional life, given the fact there were no letters found between Palma and this American institution. That epistolary exchange covered a decade (between 1907 and 1917).Finally we get to know other Peruvians who were members of this institution, including the most recent honoree in 2015.